Ion flow characteristic under UHVDC transmission line at high altitude. Issue 16 (31st January 2019) - Ya, Mou; Yu, Zhanqing; Li, Min; Wang, Xiaorui; Yang, Xi; Li, Guohua
Abstract : Among the electromagnetic environment parameters, corona current is of great significance to the evaluation of the state of the power system. However, there are few studies on the corona characteristics of high altitude transmission lines at home and abroad. Based on the ultra high‐voltage direct current (UHVDC) test line in Kunming, china, this paper studies the influence of operation voltage and environmental factors on the ionic current in UHVDC transmission lines at high altitudes, and studies the long‐term statistics of the lateral distribution of ion flow density.